'Does it Work?' – Work for Whom? Britain and Political Conditionality since the Cold War. (November 2015) - Fisher, Jonathan
Highlights: We examine the changing rationales behind UK political conditionality since 1991. UK officials no longer believe that the instrument can deliver policy change abroad. Conditionality is now used mainly for domestic, 'expressive' purposes by DFID. This shift results from changes in DFID's sociology and Britain's political economy. Conditionality's 'effectiveness' must be assessed differently in this new context. Summary: Evaluations of the political conditionality (PC) phenomenon have long focused on the question of instrumental efficacy – whether PC promotes policy reform in developing states. Evidence from the UK nevertheless suggests that this emphasis is misplaced and that donor officials increasingly use PC for 'expressive' reasons – to signal their putative commitment to delivering 'value for money' in a difficult international economic climate. This shift in rationale raises important questions; not least, what do we know about the effects of PC on public perceptions of aid and to what extent, within this dispensation, can contemporary PC be viewed as a 'success'?